G-C3N4 modified Bi2O3 composites with enhanced visible-light photocatalytic activity. (January 2015) - Li, Yeping; Wu, Shilong; Huang, Liying; Xu, Hui; Zhang, Rongxian; Qu, Minglan; Gao, Qiang; Li, Huaming
Abstract: Novel g-C3 N4 modified Bi2 O3 (g-C3 N4 /Bi2 O3 ) composites were synthesized by a mixing-calcination method. The samples were characterized by thermogravimetry (TG), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), transmission electron microscopy (TEM), UV–vis diffuse reflection spectroscopy (DRS), photoluminescence (PL) and photocurrent-time measurement (PT). The photocatalytic activity of the composites was evaluated by degradation of Rhodamine B (RHB) and 4-chlorophenol (4-CP) under visible light irradiation (>400 nm). The results indicated that the g-C3 N4 /Bi2 O3 composites showed higher photocatalytic activity than that of Bi2 O3 and g-C3 N4 . The enhanced photocatalytic activity of the g-C3 N4 /Bi2 O3 composites could be attributed to the suitable band positions between g-C3 N4 and Bi2 O3 . This leads to a low recombination between the photogenerated electron–hole pairs. The proposed mechanism for the enhanced visible-light photocatalytic activity of g-C3 N4 /Bi2 O3 composites was proven by PL and PT analysis. Highlights: Novel g-C3 N4 /Bi2 O3 composites were synthesized by a mixing-calcination method. The g-C3 N4 /Bi2 O3 composites show high visible-light photocatalytic performance. The enhanced photocatalytic activity is mainly attributed to effective separation of electron and hole.